A Phenomenological Study of the Educational Experiences of Black Women: Learning as You Go - Eva Young; Mary Ziegler; Kathy Greenberg (Adult Education Research Conference, 2008)
This research study provided a descriptive picture of educational experiences of three sets of Black sisters who grew up in the inner-city. A qualitative existential-phenomenological research study design was used to derive common themes that represented the universal essence of the participants’ experiences. This study illuminated the formal and informal learning experiences of Black women and the profound role cultural experiences of family and community play in shaping their learning experiences through adulthood. Findings suggest that the educational experiences of Black women influenced their development, voice, self-esteem, and self-defined achievement and success. These findings dispute adult development theories that suggest learning or development must precede or trail the other.
Keywords: adult development; adult learning; Black women; phenomenology